A Simple Photometer and Chemometrics Analysis for Quality Control of Sambiloto (Andrographis paniculata) Raw Material - Rudi Heryanto; Derry Permana; Aryo Tedjo; Eti Rohaeti; Mohamad Rafi; Latifah Kosim Darusman (The Journal of Pure and Applied Chemistry Research, 2017)
In this paper, we described the use of a light emitting diode (LED)-based photometer and chemometric analysis for quality control of king of bitter or sambiloto (Andrographis paniculata) raw material. The quality of medicinal plants is determined by their chemical composition. The quantities of chemical components in medicinal plants can be assessed using spectroscopic technique. We used an “in house” photometer to generate spectra of sambiloto. The spectra were analyzed by chemometric methods, i.e. principal component analysis (PCA) and partial least square discriminant analysis (PLS-DA), with the aim of herbal quality classification based on the harvesting time. From the results obtained, based on thin layer chromatography analysis, sambiloto with different collection times (1, 2, and 3 months) contained different amounts of active compounds. Evaluation of sambiloto, using its spectra and chemometric analysis has successfully differentiated its quality based on harvesting time. PCA with the first two PC’s (PC-1 = 60% and PC-2 = 35%) was able to differentiate according to the harvesting time of sambiloto. Three models were obtained by PLS-DA and could be used to predict unknown sample of sambiloto according to the harvesting time